Effects of tool geometry on tungsten removal behavior during nano-cutting. (1st July 2022) - Wang, Hao; Dong, Zhigang; Yuan, Song; Guo, Xiaoguang; Kang, Renke; Bao, Yan
Highlights: Plastic deformation mechanism of tungsten is phase transition and dislocation slip. Plastic deformation mechanism can be changed by tool geometry during nano-cutting. 1/2<111> dislocation presents compressive stress and 〈100〉 dislocation presents tensile stress. Microscopic removal behavior induced by changing of tool geometry is revealed. The selection basis of tool geometry at different machining requirements is given. Abstract: Although the researches in effects of tool geometry on the removal behavior of many metals have been studied, the deformation and removal mechanisms of tungsten have changed greatly due to the higher brittleness of tungsten compared with other metals and the research on the removal behavior of tungsten involved changing of tool geometry during nano-cutting has not been reported, which limits the development of high precision manufacturing of tungsten components. Herein, molecular dynamics (MD) simulation model of nano-cutting tungsten was established, and the material removal behavior induced by changing of tool geometry was comprehensively studied. The results showed that a larger positive rake angle or larger clearance angle or smaller edge radius of the tool was beneficial to reduce the surface roughness, elastic recovery, thickness of subsurface damage layer, cutting force, cutting temperature, friction coefficient, and maximum stress while the surface presented less residual compressive stress or even tensile stress. In the plastic deformation dominated by phase transition and dislocation slip, the region of 1/2<111> dislocation line presented compressive stress state whereas the region of <100> dislocation line presented tensile stress state during nano-cutting tungsten. Meanwhile, there was no phase transition from BCC structure to other crystal structures, but rather from ordered structure to disordered structure (amorphous structure). The correlation between amorphous phase transition and dislocation slip was affected by the tool geometry owing to the fact that the temperature and stress were different under different tool geometries. The research findings provide a comprehensive theoretical basis for the micro removal behavior of tungsten and technical reference for the design of tools in nano-cutting. Graphical abstract: Image, graphical abstract